Complications of anatomical endoscopic enucleation of the prostate - Wei, Yong; Ke, Zhi‐Bin; Xu, Ning; Xue, Xue‐Yi (Andrologia, 2020)
Transurethral resection of the prostate (TURP) remains the ‘gold standard’ for surgical treatment of benign prostatic obstruction (BPO). Recently, anatomical endoscopic enucleation of the prostate (AEEP) using holmium laser, thulium laser and plasma, etc., is extensively applied in clinical practice. However, perioperative complications of AEEP are inevitable in spite of lower incidence compared with TURP. This study reviewed the literature related to the aetiology, prevention and treatment of common complications of AEEP, which would contribute to the diagnosis and treatment of BPO.